Деформування складених індукторів із допоміжним екраном при магнітно-імпульсній обробці - Морачковський, Олег Костянтинович; Лавінський, Денис Володимирович (Вінницький національний аграрний університет, 2017)
У статті розглядається пружно-пластичне деформування складеного індуктора із допоміжним екраном та заготовки при магнітно-імпульсній обробці. Наведені умови контактної взаємодії. В якості чисельного методу розв'язання використовується метод скінчених елементів. Контактна взаємодія моделюється шляхом введення спеціальних шарів контактних елементів. Одержані просторово-часові розподіли характеристик електромагнітного поля та процесу деформування. Представлені деякі результати, які дозволяють робити певні рекомендації щодо проектування та застосування технологічних операцій подібного класу.

A large number of technical and technological facilities work under the action of electromagnetic fields. In electroconductive bodies have significant largest electromagnetic forces that can cause movement or deformation of structural elements. The creation of effective methods of analysis of the distribution of the electromagnetic field and coupled inelastic deformation of structural elements is topical at present time. The article contains a mathematical formulation of the contact problem of inelastic deformation of structural elements under the action of electromagnetic fields. Coupling of electromagnetic field and mechanical field is carried out with the help of local electromagnetic forces. Further made the transition to a variational formulation on the basis of the task of finding the minimum of the total energy of the system, which includes the energy of the electromagnetic field. For the numerical solution the finite element method is used. Nodal unknowns in this case are the magnetic vector potential and displacements. The proposed method is applied to non-stationary deformation of the "inductor-billet" technological operation of magnetic-pulse processing of metals. Some results of the deformation are presented.
Deformation of composed coils with assistant screen under the electromagnetic forming
Keywords: пружно-пластичне деформування; електромагнітне поле; метод скінчених елементів; контактна взаємодія; магнітно-імпульсна обробка; inelastic deformation; electromagnetic field; finite element method; contact interaction; magnetic-pulse processing